Historical-Critical Dictionary of Marxism : A Selection - Haug, Wolfgang Fritz 1936- HerausgeberIn; Haug, Frigga 1937- HerausgeberIn; Jehle, Peter 1954- HerausgeberIn; Küttler, Wolfgang 1936-2024 HerausgeberIn; Baehrens, Konstantin 1984- HerausgeberIn; Koivisto, Juha HerausgeberIn; Strazzeri, Victor HerausgeberIn (Historical materialism book series, 2023)
The Historical-Critical Dictionary of Marxism (HCDM) is a comprehensive Marxist lexicon, which in the 9 German-language volumes concluded so far has involved over 800 scholars from around the globe. Conceived by philosopher Wolfgang Fritz Haug in 1983, the first volume of the ongoing lexicon project was published in 1994. This first English-language selection introduces readers to the HCDM’s wide range of terms: besides Marxist concepts, approached from a plural standpoint and stressing feminist, ecological, and internationalist perspectives, it boasts entries on the histories of social movements, theoretical schools, as well as cultural, political, philosophical, and aesthetic debates. Contributors are: Samir Amin, Jan Otto Andersson, Konstantin Baehrens, Lutz-Dieter Behrendt, Mario Candeias, Robert Cohen, Alex Demirović, Klaus Dörre, William W. Hansen, Wolfgang Fritz Haug, Frigga Haug, Peter Jehle, Juha Koivisto, Wolfgang Küttler, Morus Markard, Eleonore von Oertzen, Christof Ohm, Rinse Reeling Brouwer, Jan Rehmann, Thomas Sablowski, Peter Schyga, Victor Strazzeri, Peter D. Thomas, André Tosel, Michael Vester, Lise Vogel, and Victor Wallis